Implementation Analysis of Hospital Occupational Safety and Health (K3RS) Program using the PDCA (Plan-Do-Check-Act) Method at RSUD Al-Ihsan, West Java - Adnin , Kamalia; Susanti, Ai Susi (Journal of Scientific Insights, 2024)
Occupational accidents in the hospital environment are very complex and high-risk. So the K3RS program must be implemented to protect the safety and health of staff, patients, and visitors. This study aims to analyze the Implementation of the Hospital Occupational Safety and Health Program (K3RS) using the PDCA (Plan-Do-Check-Action) method at Al-Ihsan Hospital, West Java. The technique used is descriptive research with a qualitative approach. The research informants were selected using purposive sampling, involving individuals with authority and relevant knowledge regarding OHSRS at Al-Ihsan Hospital West Java. The informants came from various positions, including the Head of Hospital Occupational Safety and Health Installation, the Head of the Disaster Prevention and Control Unit, and the Head of the Occupational Safety and Health Unit. Through the PDCA method, the OHSRS program is evaluated and improved on an ongoing basis, from planning preventive measures, implementing safety measures, and examining effectiveness, to corrective action and improvement. The results showed that the implementation of PDCA in the OHSRS program had a significant positive impact on fire prevention and suppression efforts, as well as improving the safety of staff, patients, and visitors. This study also presents suggestions for further optimization of the PDCA program to improve the management of all risks in the hospital environment.